Effects of the Opioid System Modulator, Samidorphan, on Measures of Alcohol Consumption and Patient‐Reported Outcomes in Adults with Alcohol Dependence. (13th August 2018) - O'Malley, Stephanie S.; Todtenkopf, Mark S.; Du, Yangchun; Ehrich, Elliot; Silverman, Bernard L.
Abstract : Background: Demonstrating clinically meaningful benefits of alcohol use disorder treatments is challenging. Methods: We report findings from a 12‐week, phase 2, randomized, double‐blind, placebo‐controlled study of samidorphan (1, 2.5, or 10 mg/d) in adults with alcohol use disorder (NCT00981617). The primary end point was percentage of subjects with no heavy drinking days (PSNHDD) during weeks 5 to 12; secondary end points included alcohol consumption measures, craving, and patient‐rated outcomes. Results: Altogether, 406 patients were included in the full analysis set (101, 104, 100, and 101 in the placebo, samidorphan 1, 2.5, and 10 mg treatment groups, respectively). There was no statistical difference between samidorphan and placebo groups on PSNHDD during weeks 5 to 12. However, dose‐dependent reductions in cumulative rate of heavy drinking days were observed (−41%, p  <   0.001 for samidorphan 10 mg/d vs. placebo; −30 and −32% for samidorphan 2.5 and 1 mg, p  <   0.05 for both). A higher percentage of samidorphan‐ than placebo‐treated patients had a ≥2‐category downshift in World Health Organization (WHO) risk levels of drinking. There were significant reductions from baseline with samidorphan versus placebo in alcohol craving (for samidorphan 10 mg: −38.2 [standard error: 2.9] vs. placebo: −30.2 [2.8]; p  =   0.044). On a Patient Global Assessment of Response to Therapy (PGART), samidorphan 10 mg was superior to placebo at 4, 8, and 12 weeks ( p  <   0.001, p  < 0.001, p  <   0.01, respectively). Improvement in PGART correlated with a reduction in craving and a decrease in WHO risk level. Conclusions: Results for the primary outcome measure PSNHDD were negative, but at variance with other measures and patient treatment perceptions that may be relevant for interventional studies. These findings highlight the importance of understanding the most relevant outcomes to patients and incorporating and prioritizing patient‐centered outcomes when assessing interventions for alcohol use disorder. Abstract : Independent of typically used endpoints, higher positive patient‐reported outcomes as measured by the Patient Global Assessment of Response to Therapy (PGART) scale, over the course of the study were reported by patients receiving study drug (samidorphan) than those receiving placebo, and highlight the importance of understanding outcomes most relevant to patients and prioritizing these patient‐centered outcomes in assessing interventions for alcohol use disorder.